Advanced Stage Breast Sarcoma Treatment in a Third World Country Public Hospital - Amanda Lino de Faria; Cinthia Moreno Garcia; Gabriela de Andrade Rodrigues; Lais Helena Dumbra Toloni dos Santos; Gabriela B. K. Uyeda; Simone Elias; Marair G. F. Sartori; Afonso Celso Pinto Nazário; Gil Facina (Hindawi Limited, 2018)
The case reports a 49-year-old patient, drug-addicted, undernourished, and homeless, who was referred to our service presenting a diagnostic of breast sarcoma and ulcerating tumor which extended from the right breast to the right flank. She underwent hygienic mastectomy and, as it developed, she presented a range of complications, culminating in the recurrence of the tumor and pulmonary metastasis few months after her initial treatment. There is relevance in our study not only because it reports the development of the breast sarcoma, rare neoplasm, and its aggressiveness with fast recurrence, but also because it exposes the impact of biopsychosocial behavior of this patient in her clinical outcome.